Avaliação do processo sequencial de hidrólise e liquefação hidrotérmica do sabugo de milho - Vieira, João Cláudio Martins (2022)
The growing energy demand and limitations in the use of fossil fuels encourage the research of different renewable energy sources, such as agro-industrial residues. The corn crop in Brazil corresponds to 40% of the national grain production, generating significant amounts of waste such as leaves, straw, stalks, and cobs, potential sources of selected chemical products and energy that became the focus of different studies for their valorization. Therefore, sequential hydrolysis and hydrothermal liquefaction (HTL) of corn cob were investigated, in which hydrolysate samples were collected during the hydrolysis step prior to HTL. The biomass was characterized by physicochemical methods, elemental analysis and by Fourier Transform Infrared Spectrophotometry (FT-IR). An experimental unit in semi-continuous regime was developed to research the optimal parameters for bio-oil production at 15 MPa. The influence of hydrolysis temperature (230 and 260°C), and volumetric flow rate (5 and 10 mL.min-1) on the yields and kinetic profiles (0-15 min) of hydrolysates were evaluated using High Performance Liquid Chromatography (HPLC). The influence of HTL temperature (300 and 350 °C) and volumetric flow rate (5 and 10 mL.min-1) on the yields and chemical profiles of the solid product (hydro-char) was evaluated by elemental analysis and FT-IR, and of the liquid product (bio-oil), by Gas Chromatography coupled to Mass Spectrometry (GC-MS) to analyze the composition and chemical profile of the products generated between the two routes. The highest concentrations of sugars (7.49 ± 1.97 g.L-1) and organic acids (9.35 ± 3.46 g.L-1) were observed at 260 °C and 5 mL.min-1 conditions, while that of inhibitors (7.64 ± 1.87 g.L-1) were observed at 230 °C and 5 mL.min-1 conditions. Sampling hydrolysates in the sequential process resulted in lower overall yield compared to HTL. The elemental composition of the hydro-char produced by the sequential process and the HTL were similar, as well as the higher heating value (26.06 and 26.15 MJ.kg-1, respectively); a higher concentration of oxygenated organic groups was observed in the hydro-char from the sequential process. The bio-oil produced by the sequential process exhibited a higher concentration of nitrogenous and oxygenated compounds than that produced in the HTL.